Impact of Landuse Change to Erosion at Cidanau Watersheed, Banten - K. MUNIBAH; SANTUN R.P. SITORUS; E. RUSTIADI; K. GANDASASMITA; . HARTRISARI (Jurnal Tanah dan Iklim (Indonesian Soil and Climate Journal), 2010)
Landuse is a manifestation of relationship between human activities and environmental changes, like erosion. Impact of landuse change to erosion was already happened, such as decreasing of soil fertility, flood at low land. An anticipation of landuse change was one of several alternatives that can minimize erosion. The objectives of this research were to analyze the impact of landuse change and to create the recommendation of landuse that can minimize erosion. Prediction map of landuse on 2018 and 2030 were obtained from previous research. Erosion rate were caluculated based on Universal Soil Loss Equation (USLE). This research predicted that landuse change could increase erosion rate, with asumsion if no change in term of RKLS values. The actual erosion rate (A) were 149,7 t ha-1 year-1 (2006), 154,4 t ha-1 year-1 (2018), and 159,2 t ha-1 year-1 (2030). This erosion rate were 3,7-4,9 times bigger than the tolerable erosion rate (TSL = 40 t ha-1 year-1). Modification of C and P values could minimize the actual erosion rate (A) until less than the tolerable erosion rate (A<TSL). Results of this research could be used as input for landuse planning, especially for landuse that would increase erosion rate.